Modern Education and Women's Empowerment as Constructs of Islamic Education in K.H. Ahmad Dahlan - Muhamad Slamet Yahya (Edumaspul: Jurnal Pendidikan, 2023)
Looking at historical facts about the lack of freedom of thought that was created in the implementation of national education during pre- and post-colonialism, it provoked K.H. Ahmad Dahlan to participate in raising awareness of critical thinking for the nation's children. Even though the context of the problems and challenges are relatively different, efforts to resolve and find solutions have the same substance and are relevant today, namely how to create a free and independent education climate is a good effort. The aim of this study is to analyze KH Ahmad Dahlan's perspective in constructing Islamic education so that it is able to foster an awareness of the Indonesian people to think critically through the awareness paradigm of Paulo Freire's conscientization. This research is included in the type of library research using qualitative methods. The approach used in this study is to take a historical-philosophical approach. The result is that the construction of Islamic education in the perspective of K.H. Ahmad Dahlan who offers the concept of modern education and women's independence is one step forward towards awareness of thinking and the development of critical thinking in society, and has reached the stage of critical awareness as revealed by Freire